2010
DOI: 10.1051/0004-6361/200912908
|View full text |Cite
|
Sign up to set email alerts
|

The complex behaviour of the microquasar GRS 1915+105 in theρclass observed with BeppoSAX

Abstract: GRS 1915+105 was observed byBeppoSAX for about 10 days in October 2000. For about 80% of the time, the source was in the variability class ρ, characterised by a series of recurrent bursts. We describe the results of the timing analysis performed on the MECS (1.6-10 keV) and PDS (15-100 keV) data. The X-ray count rate from GRS 1915+105 showed an increasing trend with different characteristics in the various energy bands: in the bands (1.6-3 keV) and (15-100 keV), it was nearly stable in the first part of the po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Other authors (Janiuk & Czerny 2005;Massaro et al 2010) have already demonstrated that there is typically a delay between the soft and hard X-ray pulses as well as a strong relationship between the times between these two bursts and the cycle period. Because HR1 peaks at the hard pulse, we see that the hard Xray pulse lags the soft X-ray pulse by an average of 3.3 s in our observation.…”
Section: Phase Ephemeris and Folded Light Curvementioning
confidence: 92%
See 1 more Smart Citation
“…Other authors (Janiuk & Czerny 2005;Massaro et al 2010) have already demonstrated that there is typically a delay between the soft and hard X-ray pulses as well as a strong relationship between the times between these two bursts and the cycle period. Because HR1 peaks at the hard pulse, we see that the hard Xray pulse lags the soft X-ray pulse by an average of 3.3 s in our observation.…”
Section: Phase Ephemeris and Folded Light Curvementioning
confidence: 92%
“…HR1 looks rather like the mirror image of the count rate (i.e., flipped horizontally about its maximum), except that HR1 is typically single-peaked. Other instances of the ρ state have shown different behaviors, as the number and relative strengths of the peaks can vary (Massaro et al 2010;J. Neilsen et al 2011, in preparation).…”
Section: Timing Analysismentioning
confidence: 99%
“…It has been shown that hard X-ray photons tend to lag soft ones in this class (e.g. Janiuk & Czerny 2005;Massaro et al 2010). Numerical models derived from Shakura & Sunyaev 1973 which reproduce this lag can also reproduce other flaring classes seen in GRS 1915 (e.g Nayakshin et al 2000;Massaro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ρ class (heartbeat state) is a peculiar class where the source oscillates quasi-periodically between states B and C. The light curves in the ρ class have one to several peaks per ρ-cycle (e.g. Taam et al 1997;Vilhu & Nevalainen 1998;Belloni et al 2000;Massaro et al 2010). We call the ρ class with one peak per cycle the single-peaked ρ class (hereafter called ρ1 class), and the ρ class with two peaks per cycle the double-peaked ρ class (hereafter called ρ2 class).…”
mentioning
confidence: 99%